2017
DOI: 10.4149/neo_2017_611
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Tripartite Motif Containing 28 suppresses the migration, invasion and epithelial–mesenchymal transition in ovarian carcinoma cells through down-regulation of Wnt/β-catenin signaling pathway

Abstract: Tripartite motif containing 28 (TRIM28) is a transcriptional corepressor of Kruppel-associated box zinc finger protein, which has been reported to participate in carcinogenesis. Nonetheless, whether TRIM28 plays a role in the metastasis of ovarian carcinoma (OC) is unclear and requires further investigation. In this study, two OC cell lines (A2780 and OVCAR-3) with stable low expression of TRIM28 were established via RNA interference. We found that the migratory and invasive ability of TRIM28-silenced OC cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
1
10
1
Order By: Relevance
“…Xue et al24 showed that TRIM33 as a tumour suppressor that can abrogate tumour cell proliferation and tumorigenesis by degrading nuclear β‐catenin. Knockdown of TRIM28 or TRIM44 suppresses the tumorigenesis by down‐regulating the Wnt/β‐catenin signalling pathway 25, 26. β‐Catenin can also be triggered by TRIM65 via enhancement of the ubiquitination of Axin1 in the progression of hepatocellular carcinoma 27.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xue et al24 showed that TRIM33 as a tumour suppressor that can abrogate tumour cell proliferation and tumorigenesis by degrading nuclear β‐catenin. Knockdown of TRIM28 or TRIM44 suppresses the tumorigenesis by down‐regulating the Wnt/β‐catenin signalling pathway 25, 26. β‐Catenin can also be triggered by TRIM65 via enhancement of the ubiquitination of Axin1 in the progression of hepatocellular carcinoma 27.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of TRIM28 or TRIM44 suppresses the tumorigenesis by down-regulating the Wnt/β-catenin signalling pathway. 25,26 β-Catenin can also be triggered by TRIM65 via enhancement of the ubiquitination of Axin1 in the progression of hepatocellular carcinoma. 27 In the present study, we found that β-catenin was down-regulated by TRIM32 knockdown in SGC7901 and AGS cells and was up-regulated in MKN28 cells with TRIM32 overexpression.…”
Section: Trim32 Promotes Gastric Tumour Growth In Vivomentioning
confidence: 99%
“…Epithelial-to-mesenchymal transition (EMT) is a notable process involved in tumor-associated metastases and invasion (8). In the progress of EMT, obvious changes on cell adhesion, polarities, and motile property have been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Along that line, a molecular process potentially linking TRIM28 and BOK could be EMT. Knockdown of TRIM28 was shown to impair EMT in ovarian cancer cells by upregulation of E-cadherin (CHD1) and reduction of vimentin ( VIM ) and N-cadherin (CDH2) ( Deng et al., 2017 ). Along the same line, Chen and colleagues reported that, in NSCLCs, TGFβ-induced EMT is dependent on induction of TRIM28, strongly suggesting that TRIM28 contributes to EMT in NSCLC ( Chen et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%